Estudo fitoquímico e biológico da Capirona decorticans Spruce : identificação de flavonoides por LC-MS/MS, avaliação de atividade antioxidante e antimutagênica - Barbosa, Fernando Gomes (2017)
Capirona decorticans Spruce (C. decorticans) popularly named “perna de moça ou mulateiro” is a species with reports of its use for the treatment of warts, wounds, mycoses, scabious and added in the “Ayahuasca tea”. Although popularly used there is no research about the species. This paper aimed to perform a phytochemical study of ethanolic extract (EE) and hydromethanolic fraction (FM) of leaves of C. decorticans, such as: antiradical potential with DPPH, dosage of total phenolics and flavonoids, identification of flavonoids by LC-MS/MS and biological study through markers of oxidative stress and the mutagenic/antimutagenic effect induced by cyclophosphamide (CPA) in mice. The evaluation was made in the hepatic and renal tissues, by dosing with carbonylated proteins, ascorbic acid, catalase and reactive species of thiobarbituric acid. The evaluation of the mutagenic/antimutagenic effect was done through the Micronucleus Test. There was protein carbonylation in the liver of animals exposed to CPA that was reduced by FM, in the other markers of oxidative stress there were no toxic changes. In the Micronucleus Test the mutagenic effect of CPA was reduced by 96% in EE and 71% in FM. EE showed mutagenicity when used alone. C. decorticans presented antioxidant potential in vitro equivalent to standards in other species. It did not cause oxidative stress and toxicity to the animals and also prevented the occurrence. Mutagenicity showed a large reduction with the use of EE and FM. In isolation the EE presented mutagenicity which suggests a better evaluation of the species due to its use by the peoples.